2015
DOI: 10.1007/s10535-014-0476-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lead and nitric oxide on photosynthesis, antioxidative ability, and mineral element content of perennial ryegrass

Abstract: Hydroponics experiments were conducted to study the effects of sodium nitroprusside (SNP, a donor of NO) on lead toxicity in ryegrass (Lolium perenne L.) seedlings. When the ryegrass seedlings were grown in a nutrient solution containing 500 μM Pb 2+ for two weeks, the plant biomass as well as net photosynthetic rate, transpiration rate, chlorophyll and carotenoid content of leaves decreased. The Pb stress also induced the production of superoxide anion (O 2•− ) and hydrogen peroxide (H 2 O 2 ), leading to mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(50 citation statements)
references
References 47 publications
4
46
0
Order By: Relevance
“…Growth hormones enhance the resilience of plants to stress; they are key components for proper growth and maintenance under stressful conditions (Asgher et al 2015). The positive influence of growth hormones such as JA (Sirhindi et al 2016) and NO (Bai et al 2015;Ahmad, Abdel Latef, et al 2016) has been reported earlier as well. In the present study, application of JA and NO to NaClstressed S. lycopersicum enhanced growth and subsequent biomass accumulation, thereby depicting their active involvement in cell division and organ differentiation.…”
Section: Discussionmentioning
confidence: 76%
“…Growth hormones enhance the resilience of plants to stress; they are key components for proper growth and maintenance under stressful conditions (Asgher et al 2015). The positive influence of growth hormones such as JA (Sirhindi et al 2016) and NO (Bai et al 2015;Ahmad, Abdel Latef, et al 2016) has been reported earlier as well. In the present study, application of JA and NO to NaClstressed S. lycopersicum enhanced growth and subsequent biomass accumulation, thereby depicting their active involvement in cell division and organ differentiation.…”
Section: Discussionmentioning
confidence: 76%
“…Free proline content was determined as described by Bates et al (1973) with slight modification Proline amount was determined using the methods of Bates et al (1973) and Bai et al (2015). After extraction with 3 % (m/v) 5-sulfosalicylic acid at room temperature, proline content was determined from a standard curve and calculated on a fresh mass basis.…”
Section: Determination Of Proline Soluble Sugars and Protein Contentmentioning
confidence: 99%
“…They can function in osmotic adjustment, or act as signalling molecules to activate some specific transduction pathways (Misra et al 2009). Secondary stresses such as oxidative damage often occur (Mittler et al 2002, Xu et al 2015 as a consequence of excess production of ROS. To counteract the oxidative stress, both enzymatic and non-enzymatic antioxidants have evolved in plants (Zheng et al 2009a, Lin et al 2012.…”
Section: Introductionmentioning
confidence: 99%
“…Plants carry a defence mechanism to counter HM stresses, which increase antioxidant enzyme activities such as catalase (CAT, EC 1.11.1.6) or per oxidases (POD, EC 1.11.1.7) [18]. However, the reaction of plants to HMs is generally under the environmental influence of plant genotype [4].…”
Section: Determining Antioxidant Activitymentioning
confidence: 99%